GLP-1 Mediates Antiapoptotic Effect by Phosphorylating Bad through a β-Arrestin 1-mediated ERK1/2 Activation in Pancreatic β-Cells - Quoyer, Julie (American Society for Biochemistry and Molecular Biology, 2010)
Strategies based on activating GLP-1 receptor (GLP-1R) are intensively developed for the treatment of type 2 diabetes. The exhaustive knowledge of the signaling pathways linked to activated GLP-1R within the β-cells is of major importance. In β-cells, GLP-1 activates the ERK1/2 cascade by diverse pathways dependent on either Gα(s)/cAMP/cAMP-dependent protein kinase (PKA) or β-arrestin 1, a scaffold protein. Using pharmacological inhibitors, β-arrestin 1 small interfering RNA, and islets isolated from β-arrestin 1 knock-out mice, we demonstrate that GLP-1 stimulates ERK1/2 by two temporally distinct pathways. The PKA-dependent pathway mediates rapid and transient ERK1/2 phosphorylation that leads to nuclear translocation of the activated kinases. In contrast, the β-arrestin 1-dependent pathway produces a late ERK1/2 activity that is restricted to the β-cell cytoplasm. We further observe that GLP-1 phosphorylates the cytoplasmic proapoptotic protein Bad at Ser-112 but not at Ser-155. We find that the β-arrestin 1-dependent ERK1/2 activation engaged by GLP-1 mediates the Ser-112 phosphorylation of Bad, through p90RSK activation, allowing the association of Bad with the scaffold protein 14-3-3, leading to its inactivation. β-Arrestin 1 is further found to mediate the antiapoptotic effect of GLP-1 in β-cells through the ERK1/2-p90RSK-phosphorylation of Bad. This new regulatory mechanism engaged by activated GLP-1R involving a β-arrestin 1-dependent spatiotemporal regulation of the ERK1/2-p90RSK activity is now suspected to participate in the protection of β-cells against apoptosis. Such signaling mechanism may serve as a prototype to generate new therapeutic GLP-1R ligands.